Magnetic polymer composite material with efficient photothermal effect and application thereof

By using high-efficiency photothermal effect magnetic polymer composite materials in seawater desalination technology, using photothermal effect to drive evaporation and condensation, and through magnetic field separation and recycling, the problems of low efficiency, easy material damage and secondary pollution in the existing technology are solved, and efficient and environmentally friendly seawater desalination effect is achieved.

CN119613823APending Publication Date: 2025-03-14JIANGSU XFNANO MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868854.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing seawater desalination technology is inefficient, the materials are easily damaged by the environment, and are difficult to separate and recycle, resulting in secondary pollution.

Method used

Magnetic polymer composite materials with high efficiency photothermal effect were designed and prepared. By dispersing magnetic purple phosphorus nanosheets modified by polyphosphazene in a hydrogel matrix, the evaporation and condensation of water are driven by the photothermal effect, seawater desalination is achieved, and separated and recovered through a magnetic field.

Benefits of technology

It achieves efficient seawater desalination, improves production efficiency, avoids secondary pollution, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613823A_ABST
    Figure CN119613823A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic polymer composite material with an efficient photothermal effect and application thereof. The magnetic polymer composite material with the efficient photothermal effect is prepared by loading nanoparticles with proper magnetism and stability on purple phosphorus nanosheets with the photothermal effect and then dispersing the nanoparticles into a polymer matrix with excellent mechanical property and stability. The purple phosphorus nanosheet can efficiently convert light energy into heat energy, and the polymer matrix not only can maintain the structural integrity in the compounding process, but also can provide a porous skeleton structure for the composite material. The composite material can be used for seawater desalination treatment, solar energy can be converted into heat energy through a light absorption material, then the evaporation and condensation process of water is driven, and therefore seawater desalination is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a magnetic polymer composite material with high-efficiency photothermal effect and application thereof. Background Art

[0002] Water shortage has become one of the most serious challenges facing human society. About 70% of the earth's surface is covered by oceans. Desalination of seawater can provide fresh water resources for humans and solve the problem of water shortage. Desalination of seawater refers to the process of removing salt from seawater and converting it into fresh water through various technical means. The main methods include electrodialysis, reverse osmosis, distillation, etc. These methods generally desalinate seawater by absorbing salt ions or evaporating. They are inefficient and have many technical defects, including:

[0003] (1) The efficiency of using only a single desalination method such as evaporation and matrix filtration of salt ions is low. Due to the large amount of impurities in seawater, the complex and diverse salts, and the extreme acid-base environment, it is difficult to desalinate seawater to a more ideal state by a single method.

[0004] (2) The materials cannot be separated when used for seawater desalination, causing secondary pollution to the seawater.

[0005] (3) Existing composite materials are subject to environmental restrictions during actual use. Long-term exposure to seawater will cause the materials to be damaged and the desalination process cannot continue.

[0006] Therefore, it is urgent to develop a multifunctional composite material that is less affected by the environment and easy to separate. The present invention designs and prepares a magnetic polymer composite material with high efficiency photothermal effect, which can not only use light absorption materials to convert solar energy into thermal energy, but also drive the evaporation and condensation process of water to achieve seawater desalination. At the same time, the material can be separated and recycled through a magnetic field. Using it for seawater desalination can not only improve production efficiency, but also avoid secondary pollution of water quality. Summary of the invention

[0007] One of the purposes of the present invention is to provide a magnetic polymer composite material with high efficiency photothermal effect, which is prepared by the following steps:

[0008] Step 1, mixing purple phosphorus crystal powder and solvent water in a mass ratio of 1g:100-1000ml, ultrasonically peeling, taking the upper suspension after centrifugation, drying to obtain purple phosphorus nanosheets, and dispersing them in water to obtain a purple phosphorus nanosheet dispersion;

[0009] Step 2, adding divalent iron salt and trivalent iron salt to the purple phosphorus nanosheet dispersion at a molar ratio of 1.4-1.9:0.8-1.2, adding polyethylene glycol, stirring and mixing, adjusting the pH value to alkaline, reacting in an oil bath, washing the reactants to neutrality, and obtaining magnetic purple phosphorus nanosheets;

[0010] Step 3, dispersing the magnetic purple phosphorus nanosheets in a solvent, adding hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone to 4% triethylamine by volume, then dropping the triethylamine into the magnetic purple phosphorus nanosheet solution, heating for reaction, and obtaining polyphosphazene-coated magnetic purple phosphorus nanosheets;

[0011] The ratio of the magnetic purple phosphorus nanosheets, hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone is 100 mg: 0.1 mol: 0.3 mol;

[0012] Step 4, dissolving the polyphosphazene-coated magnetic purple phosphorus nanosheets in a calcium chloride aqueous solution, then dropping a sodium alginate aqueous solution therein, stirring to form an emulsion, applying a magnetic field, and then performing a cross-linking reaction to obtain the magnetic polymer composite material with a high-efficiency photothermal effect;

[0013] The mass ratio of the polyphosphazene-coated magnetic purple phosphorus nanosheets, calcium chloride and sodium alginate is 1:4:1.

[0014] Furthermore, in step 3, the solvent is selected from tetrahydrofuran, dichloromethane or chloroform.

[0015] Furthermore, the heating reaction condition in step 3 is 250° C. for 5 hours.

[0016] Furthermore, in step 4, the intensity of the magnetic field is 0.1T to 2T.

[0017] Furthermore, the conditions of the cross-linking reaction are 50° C. to 60° C., 10 min to 30 min, and standing reaction.

[0018] The second object of the present invention is to provide the application of the above-mentioned magnetic polymer composite material with high efficiency photothermal effect in seawater desalination treatment.

[0019] The present invention selects purple phosphorus nanosheets with photothermal effect to load nanoparticles (Fe3O4) with appropriate magnetism and stability, and then disperses the nanoparticles in a polymer matrix with excellent mechanical properties and stability, so as to prepare a magnetic polymer composite material with high-efficiency photothermal effect; the purple phosphorus nanosheets can efficiently convert light energy into heat energy, and the polymer matrix can not only maintain the integrity of the structure during the composite process, but also provide a porous skeleton structure for the composite material, which can be used to filter salt ions.

[0020] During the preparation process, magnetic purple phosphorus nanosheets (purple phosphorus nanosheets loaded with ferroferric oxide nanoparticles) are combined with polyphosphazene, and polyphosphazene can be coated on the surface of purple phosphorus nanosheets loaded with ferroferric oxide nanoparticles to form a protective film; during the hydrogel molding process, the prepared polyphosphazene-coated magnetic purple phosphorus nanosheets are dispersed in the hydrogel matrix, and a magnetic field is applied. Through the magnetic field-induced self-assembly process, the magnetic purple phosphorus nanosheets can present an ordered arrangement structure in the composite material, and this ordered structure helps to improve the photothermal effect and magnetic properties of the composite material.

[0021] Among them, the hydrogel-encapsulated polyphosphazene composite magnetic purple phosphorus nanosheets mainly use the cross-linking emulsification method to disperse the polyphosphazene-encapsulated magnetic purple phosphorus nanosheet composite material into the hydrogel matrix. Hydrogel, as a soft material matrix, can support and fix these composites. The cross-linking reaction is induced by adding a cross-linking agent and adjusting the reaction temperature. Subsequently, an external magnetic field is applied, and the directional arrangement induced by the magnetic field is maintained during the cross-linking reaction. Since the magnetic purple phosphorus nanosheets are magnetic, they will be oriented under the action of the magnetic field. This arrangement will proceed along the direction of the magnetic field lines, thereby promoting the composite to form a material with a porous skeleton structure. This porous skeleton structure is mainly composed of purple phosphorus nanosheets, ferrosoferric oxide nanoparticles and polymer chains.

[0022] The present invention optimizes the performance of the composite material by adjusting the ratio of magnetic nanoparticles, purple phosphorus nanosheets and hydrogel, as well as the process parameters in the preparation process; wherein the specific ratio is affected by the material properties and the preparation process, the mass fraction of the magnetic nanoparticles is between 1% and 20%, the mass fraction of the purple phosphorus nanosheets is between 1% and 10%, and the mass fraction of the polymer material is between 70% and 98%.

[0023] The composite material prepared by the present invention can be separated and recovered by a magnetic field under laboratory conditions. In the process of seawater desalination, this means that these materials can be easily removed from the desalinated water, thereby avoiding secondary pollution of the water quality. In addition, this magnetic separation characteristic also allows these materials to be easily maintained and replaced during long-term use. In the process of seawater desalination, the composite material needs to withstand various harsh environmental conditions, such as high temperature, high salinity and strong ultraviolet radiation. The polymer matrix can effectively protect the photothermal conversion components from these conditions, thereby extending the service life of the composite material.

[0024] Compared with the prior art, this application has the following beneficial effects:

[0025] 1. The magnetic polymer composite material with high-efficiency photothermal effect provided by the present invention disperses polyphosphazene-modified magnetic purple phosphorus nanosheets in a hydrogel matrix, so that the composite material not only has photothermal effect, but also has magnetic responsiveness and superparamagnetism. It can be magnetically separated after use, avoiding secondary pollution and can be reused.

[0026] 2. The magnetic polymer composite material with high-efficiency photothermal effect provided by the present invention uses polyphosphazene to surface-coat the magnetic purple phosphorus nanosheets, which not only enhances the interaction between the magnetic purple phosphorus nanosheets and the hydrogel precursor, but also helps to prevent the agglomeration and sedimentation of the nanoparticles, so that the magnetic purple phosphorus nanosheets are more stably dispersed in the hydrogel matrix, thereby improving the stability of the composite material; at the same time, it can also effectively prevent the penetration of harmful substances such as water and oxygen, thereby extending the service life of the magnetic purple phosphorus nanosheets.

[0027] 3. The magnetic polymer composite material with efficient photothermal effect provided by the present invention introduces a magnetic field during the cross-linking reaction of polyphosphazene composite magnetic purple phosphorus nanosheets and hydrogel to form a uniform and orderly arrangement structure, which makes the composite material have higher mechanical strength and better stability. At the same time, the porous skeleton structure formed by the cross-linking reaction helps to prevent cracks and breakages in the composite material during use, thereby improving its durability. Secondly, the formation of the porous skeleton structure also helps to increase the specific surface area of ​​the composite material, increase its contact area with seawater, increase the efficiency of filtering salt ions, and improve the desalination effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscope image of the magnetic purple phosphorus nanosheet of the present invention.

[0029] Figure 2 This is a saturation magnetization curve of Example 1.

[0030] Figure 3 This is a saturation magnetization curve diagram of Example 2.

[0031] Figure 4 This is a saturation magnetization curve diagram of Example 3. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0035] The seawater samples used in the following examples and comparative examples were collected from the Yellow Sea using a stratified water sampler on October 5, 2024. The seawater samples were tested by ICP at room temperature and pressure using an Agilent 720 inductively coupled plasma emission spectrometer. The test data are as follows:

[0036]

[0037] Example 1

[0038] (1) 1 g of purple phosphorus crystal powder was exfoliated in 1000 ml of deionized water in an ice bath at 1000 W for 8 h, and then centrifuged at 3500 rpm for 10 min. The upper suspension was taken and dried to obtain about 500 mg of purple phosphorus nanosheets, which were resuspended in 500 ml of deionized water to obtain a 1 mg / ml purple phosphorus nanosheet dispersion.

[0039] (2) Disperse 1.35g of ferric chloride hexahydrate and 2g of ferrous chloride tetrahydrate in 100ml of 1mg / ml purple phosphorus nanosheet dispersion, add 100ml of ethanol and 2g of PEG2000, and stir magnetically at room temperature for half an hour at 500rpm. After uniform stirring, drip ammonia water to adjust the pH to 10, react in an oil bath at 80℃ for 3h, centrifuge and wash the reaction product until it is neutral, and dry it at 60℃ overnight to obtain a dried product, which is magnetic purple phosphorus nanosheet.

[0040] (3) 100 mg of magnetic purple phosphorus nanosheets were dispersed in 100 ml of chloroform, and 0.1 mol of hexachlorocyclotriphosphazene and 0.3 mol of 4,4'-dihydroxydiphenyl sulfone were added to 50 ml of triethylamine with a volume fraction of 4%. After stirring and dissolving evenly, the mixture was dropped into the magnetic purple phosphorus nanosheet solution. The mixture was then reacted at 250° C. for 5 h under vacuum conditions. After cooling to room temperature, the reaction solution was taken out and washed twice by centrifugation with ethanol and water respectively (the centrifugation condition was 8000 rpm, 5 min). The precipitate was the polyphosphazene-coated magnetic purple phosphorus nanosheets.

[0041] (4) 100 mg of polyphosphazene-coated magnetic purple phosphorus nanosheets and 400 mg of calcium chloride were dissolved in 100 ml of deionized water and recorded as solution 1. 100 mg of sodium alginate was dissolved in 100 ml of deionized water and stirred evenly, then solution 1 was slowly dripped into the mixture and mechanically stirred evenly at a speed of 200 rpm until an emulsion was formed. A 0.5 T magnetic field was applied and the mixture was allowed to stand in a water bath at 60°C for 30 min to cross-link and form a hydrogel. After the reaction, the reaction product was placed in a dialysis bag and dialyzed three times (30 min each time) in a 500 ml mixed solution of ethanol and water in a volume ratio of 1:1. The product in the dialysis bag was then collected to obtain sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets.

[0042] The obtained sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets is used for seawater desalination treatment. The specific process is: put the prepared composite material into a glass beaker, put 100mL of collected seawater sample into it at room temperature, and after standing for 1-3 hours, use a strong magnet to separate the composite material from the surrounding concentrated solution. After separation, put the hydrogel in a glass evaporating dish in a glass jar, use a linear Fresnel reflector with single-axis solar tracking to reflect sunlight to illuminate the evaporating dish, connect a steam condenser above the glass jar, and connect a condensation tube to connect the beaker to collect condensed desalinated seawater.

[0043] The ICP test data of desalinated seawater are as follows:

[0044]

[0045] It can be seen from the test data that the concentrations of sodium ions, magnesium ions and calcium ions in the seawater treated with the magnetic polymer composite material with high-efficiency photothermal effect prepared in this embodiment are greatly reduced, indicating that the sample has the function of desalinating seawater.

[0046] Compared with Example 2 and Example 3, this embodiment achieves the best seawater desalination effect at the same hydrogel mass.

[0047] Example 2

[0048] (1) 1 g of purple phosphorus crystal powder was exfoliated in 1000 ml of deionized water in an ice bath at 1000 W for 8 h, and then centrifuged at 3500 rpm for 10 min. The upper suspension was taken and dried to obtain about 500 mg of purple phosphorus nanosheets, which were resuspended in 500 ml of water to obtain a 1 mg / ml purple phosphorus nanosheet dispersion.

[0049] (2) Disperse 1.29g of ferric chloride hexahydrate and 2.78g of ferrous chloride tetrahydrate in 100ml of 1mg / ml purple phosphorus nanosheet dispersion, add 100ml of ethanol and 2g of PEG2000, and stir magnetically at room temperature for half an hour at 500rpm. After uniform stirring, drip ammonia water to adjust the pH to 10, react in an oil bath at 80℃ for 3h, centrifuge and wash the reaction product until it is neutral, and dry it at 60℃ overnight to obtain a dried product as magnetic purple phosphorus nanosheets.

[0050] (3) 100 mg of magnetic purple phosphorus nanosheets were dispersed in 100 ml of chloroform, and 0.1 mol of hexachlorocyclotriphosphazene and 0.3 mol of 4,4'-dihydroxydiphenyl sulfone were added to 50 ml of triethylamine with a volume fraction of 4%. After stirring and dissolving evenly, the mixture was dropped into the magnetic purple phosphorus nanosheet solution. The mixture was then reacted at 250° C. for 5 h under vacuum conditions. After cooling to room temperature, the reaction solution was taken out and washed twice by centrifugation with ethanol and water respectively (the centrifugation condition was 8000 rpm, 5 min). The precipitate was the polyphosphazene-coated magnetic purple phosphorus nanosheets.

[0051] (4) 100 mg of polyphosphazene-coated magnetic purple phosphorus nanosheets and 400 mg of calcium chloride were dissolved in 100 ml of deionized water and recorded as solution 1. 100 mg of sodium alginate was dissolved in 100 ml of deionized water and stirred evenly, then solution 1 was slowly dripped into the solution and mechanically stirred evenly at a speed of 200 rpm until an emulsion was formed. A 0.1 T magnetic field was applied and the solution was allowed to stand in a water bath at 60°C for 30 min to cross-link and form a hydrogel. After the reaction, the reaction product was placed in a dialysis bag and dialyzed three times (30 min each time) in a 500 ml mixed solution of ethanol and water in a volume ratio of 1:1. The product in the dialysis bag was then collected to obtain sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets.

[0052] Referring to the method of Example 1, the obtained sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets was used for seawater desalination treatment. The ICP detection data of the desalinated seawater liquid are as follows:

[0053]

[0054] It can be seen from the test data that the concentrations of sodium ions, magnesium ions and calcium ions in the seawater treated with the magnetic polymer composite material with high-efficiency photothermal effect prepared in this embodiment are reduced. Compared with Example 1, the desalination effect is poor, and the concentrations of sodium ions, magnesium ions and calcium ions are about 4 times that of Example 1, but the sample still has the function of desalinating seawater.

[0055] Example 3

[0056] (1) 1 g of purple phosphorus crystal powder was exfoliated in 1000 ml of deionized water in an ice bath at 1000 W for 8 h, and then centrifuged at 3500 rpm for 10 min. The upper suspension was taken and dried to obtain about 500 mg of purple phosphorus nanosheets, which were resuspended in 500 ml of water to obtain a 1 mg / ml purple phosphorus nanosheet dispersion.

[0057] (2) Disperse 1.94 g of ferric chloride hexahydrate and 3.77 g of ferrous chloride tetrahydrate in 100 ml of 1 mg / ml purple phosphorus nanosheet dispersion, add 100 ml of ethanol and 2 g of PEG2000, and stir at 500 rpm for half an hour at room temperature. After uniform stirring, drip ammonia water to adjust the pH to 10, react in an oil bath at 80° C. for 3 h, centrifuge and wash the reaction product until it is neutral, and dry it at 60° C. overnight to obtain a dried product, which is magnetic purple phosphorus nanosheets.

[0058] (3) 100 mg of magnetic purple phosphorus nanosheets were dispersed in 100 ml of chloroform, and 0.1 mol of hexachlorocyclotriphosphazene and 0.3 mol of 4,4'-dihydroxydiphenyl sulfone were added to 50 ml of triethylamine with a volume fraction of 4%. After stirring and dissolving evenly, the mixture was dropped into the magnetic purple phosphorus nanosheet solution. The mixture was then reacted at 250° C. for 5 h under vacuum conditions. After cooling to room temperature, the reaction solution was taken out and washed twice by centrifugation with ethanol and water respectively (the centrifugation condition was 8000 rpm, 5 min). The precipitate was the polyphosphazene-coated magnetic purple phosphorus nanosheets.

[0059] (4) 100 mg of polyphosphazene-coated magnetic purple phosphorus nanosheets and 400 mg of calcium chloride were dissolved in 100 ml of deionized water and recorded as solution 1. 100 mg of sodium alginate was dissolved in 100 ml of deionized water and stirred evenly, then solution 1 was slowly dripped into the solution and mechanically stirred evenly at a speed of 200 rpm until an emulsion was formed. A 2 T magnetic field was applied and the solution was allowed to stand in a water bath at 60 °C for 30 min to cross-link and form a hydrogel. After the reaction, the reaction product was placed in a dialysis bag and dialyzed three times (30 min each time) in a 500 ml mixed solution of ethanol and water in a volume ratio of 1:1. The product in the dialysis bag was then collected to obtain sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets.

[0060] Referring to the method of Example 1, the obtained sodium alginate hydrogel combined with polyphosphazene magnetic purple phosphorus nanosheets was used for seawater desalination treatment. The ICP detection data of the desalinated seawater liquid are as follows:

[0061]

[0062] It can be seen from the test data that the concentrations of sodium ions, magnesium ions and calcium ions in the seawater treated with the magnetic polymer composite material with high-efficiency photothermal effect prepared in this embodiment are reduced. Compared with Example 1, the desalination effect is poor, and the concentrations of sodium ions, magnesium ions and calcium ions are about 1.5 times that of Example 1, but the sample still has the function of desalinating seawater.

[0063] At the same time, the above three embodiments can all remain photothermal active in the collected seawater samples for 10-12 hours.

[0064] Comparative Example 1

[0065] The difference between this embodiment and embodiment 1 is that only magnetic purple phosphorus nanosheets are prepared without using hydrogel wrapping.

[0066] (1) 1 g of purple phosphorus crystal powder was exfoliated in 1000 ml of deionized water in an ice bath at 1000 W for 8 h, and then centrifuged at 3500 rpm for 10 min. The upper suspension was taken and dried to obtain about 500 mg of purple phosphorus nanosheets, which were resuspended in 500 ml of water to obtain a 1 mg / ml purple phosphorus nanosheet dispersion.

[0067] (2) Disperse 1.35g of ferric chloride hexahydrate and 2g of ferrous chloride tetrahydrate in 100ml of 1mg / ml purple phosphorus nanosheet aqueous dispersion, then add 100ml of ethanol and 2g of PEG2000, and stir magnetically at room temperature for half an hour at 500rpm. After uniform stirring, drip ammonia water to adjust the pH to 10, react in an oil bath at 80℃ for 3h, centrifuge and wash the reaction product until it is neutral, and dry it at 60℃ overnight to obtain a dried product, which is magnetic purple phosphorus nanosheet.

[0068] In this embodiment, only the photothermal effect of magnetic purple phosphorus nanosheets is used to desalinate seawater. The process is to use a linear Fresnel reflector with a single-axis sun tracking to reflect sunlight to illuminate an evaporating dish filled with seawater. 100 mL of seawater contains 100 mg of magnetic purple phosphorus nanosheets. A steam condenser is connected to the top of the glass jar, and a condenser tube is connected to a beaker to collect the condensed desalinated seawater liquid.

[0069] The ICP test data of desalinated seawater are as follows:

[0070]

[0071] It can be seen from the test data that the concentrations of sodium ions, magnesium ions and calcium ions in seawater treated with the sample (magnetic purple phosphorus nanosheets) prepared in this embodiment are reduced. Compared with Examples 1, 2 and 3, the desalination effect of the magnetic purple phosphorus nanosheets is poor, and the single existence time of this comparative example in seawater can only be 3-5 hours. Beyond this time, the efficiency of the photothermal effect is greatly reduced.

[0072] Comparative Example 2

[0073] The difference between this embodiment and embodiment 1 is that only sodium alginate hydrogel is prepared, and no polyphosphazene-coated magnetic purple phosphorus nanosheets are added.

[0074] 400 mg of calcium chloride was dissolved in 100 ml of deionized water and recorded as solution 1. 100 mg of sodium alginate was dissolved in 100 ml of deionized water and stirred evenly, then slowly dripped into solution 1, and uniformly mechanically stirred at a speed of 200 rpm to form an emulsion, and reacted in a water bath at 60°C for 30 min to cross-link to form a hydrogel. After the reaction, the reaction product was put into a dialysis bag and dialyzed three times (30 min each time) in 500 ml of a mixed solution of ethanol and water in a volume ratio of 1:1, and then the dialysis bag product was collected to obtain sodium alginate hydrogel.

[0075] In this comparative example, the prepared sodium alginate hydrogel is placed in a glass beaker, and 100 mL of the collected seawater sample is placed in it at room temperature. After standing for 1-3 hours, the complex is separated from the surrounding concentrated solution by filtering through a filter membrane, and then placed in an evaporation container with a condenser connected to the beaker, and heated with an alcohol lamp under the evaporation container, and the desalinated seawater is collected by the condenser.

[0076] The ICP test data of desalinated seawater are as follows:

[0077]

[0078] It can be seen from the test data that the concentrations of sodium ions, magnesium ions and calcium ions in the seawater treated with the sodium alginate hydrogel prepared in this embodiment are reduced. Compared with Examples 1, 2 and 3, the hydrogel does not contain magnetic purple phosphorus nanosheets, and the seawater desalination effect is poor.

[0079] In summary, Comparative Examples 1 and 2 provide the effects of desalinating seawater by two separate methods, both of which are worse than the effects of Examples 1-3, proving that the efficiency of the composite material of the present invention in desalinating seawater is higher than that of a single method.

Claims

1. A magnetic polymer composite material with high efficiency photothermal effect, characterized in that: Prepared by the following steps: Step 1, mixing purple phosphorus crystal powder and solvent water according to a mass ratio of 1g:100-1000ml, ultrasonically peeling, taking the upper suspension after centrifugation, drying to obtain purple phosphorus nanosheets, and dispersing them in water to obtain a purple phosphorus nanosheet dispersion; Step 2, adding divalent iron salt and trivalent iron salt to the purple phosphorus nanosheet dispersion at a molar ratio of 1.4-1.9:0.8-1.2, adding polyethylene glycol, stirring and mixing, adjusting the pH value to alkaline, reacting in an oil bath, washing the reactants to neutrality, and obtaining magnetic purple phosphorus nanosheets; Step 3, dispersing the magnetic purple phosphorus nanosheets in a solvent, adding hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone to 4% triethylamine by volume, then dropping the triethylamine into the magnetic purple phosphorus nanosheet solution, heating for reaction, and obtaining polyphosphazene-coated magnetic purple phosphorus nanosheets; The ratio of the magnetic purple phosphorus nanosheets, hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone is 100 mg: 0.1 mol: 0.3 mol; Step 4, dissolving the polyphosphazene-coated magnetic purple phosphorus nanosheets in a calcium chloride aqueous solution, then dropping a sodium alginate aqueous solution thereinto, stirring to form an emulsion, applying a magnetic field, and then performing a cross-linking reaction to obtain the magnetic polymer composite material with a high-efficiency photothermal effect; The mass ratio of the polyphosphazene-coated magnetic purple phosphorus nanosheets, calcium chloride and sodium alginate is 1:4:

1.

2. The magnetic polymer composite material with high efficiency photothermal effect according to claim 1, characterized in that: In step 3, the solvent is selected from tetrahydrofuran, dichloromethane or chloroform.

3. The magnetic polymer composite material with high efficiency photothermal effect according to claim 1, characterized in that: The heating reaction conditions in step 3 are 250° C. for 5 h.

4. The magnetic polymer composite material with high efficiency photothermal effect according to claim 1, characterized in that: In step 4, the strength of the magnetic field is 0.1T~2T.

5. The magnetic polymer composite material with high efficiency photothermal effect according to claim 1, characterized in that: In step 4, the conditions for the cross-linking reaction are 50° C. to 60° C., 10 min to 30 min, and standing reaction.

6. Use of the magnetic polymer composite material with high efficiency photothermal effect as claimed in any one of claims 1 to 5 in seawater desalination treatment.